Resting Heart Rate and Cardiovascular Endurance of Provincial Cricketers and Middle-Distance Runners: an Observation - Biswas, Subhashis; Biswas, Bankim; Biswas, Ankur; Bhunia, Gopinath Bhowmik (Physical Education Theory and Methodology, 2022)
Resting heart rate is a reliable biomarker for measuring fitness in terms of cardiovascular health as well as analyzing an athlete’s recovery. The study purpose was to explore the resting heart rate and cardiovascular endurance of the cricketers and middle-distance runners of West Bengal. Materials and methods. Forty male sub-elite athletes with a mean age of 19.8±2.4 years, height of 1.66±0.05 m, and body mass of 55.5±7.0 kg were randomly selected and categorized as cricketers (20) and middle-distance runners (20). Five-minute RR intervals were recorded during a resting state in the supine position using a Polar V800 smart watch along with a Polar H10 chest strap and a Polar H7 heart rate sensor. Cardiovascular endurance (predicted VO2max) was measured using the Yo-Yo intermittent recovery test Level 1. Results. Mean resting heart rate, SDNN, rMSSD, pNN50, and predicted VO2max of cricketers and middle-distance runners have been found to be 57.2±5.9 bpm, 53.5±26.6 ms, 68.4±36.8 ms, 40.9±23.2%, and 48.4±1.7 ml/kg/min and 61.7±7.3 bpm, 47.0±18.8 ms, 59.2±27.3 ms 32.4±20.9%, and 49.0±2.2 ml/kg/min, respectively. No significant difference was observed in time domain parameters and predicted VO2max, but a significant difference (p=0.033) was observed in resting heart rate of two groups. A significant negative (r= -0.62, p=<0.001) association has been observed between resting heart rate and predicted VO2max. Conclusions. The low resting heart rate of the cricketers may possibly have come from higher training load borne by the young players. Based on the players’ predicted VO2max, it looks like having good cardiovascular fitness is just as important in modern cricket as it is in middle-distance running.